The Convergence of Contour Dynamics Methods (Journal of Computational Mathematics, 1989)
In this paper the properties of contour dynamics methods of two-dimensional incompressible inviscid vortex flows are investigated. The error estimates and the convergence of the methods for piecewise constant vorticity patches using Euler's method are obtained.